2009
DOI: 10.1111/j.1365-2036.2009.04037.x
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab and other immunomodulating drugs in patients with inflammatory bowel disease and the risk of serious bacterial infections

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
3
17

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(146 citation statements)
references
References 24 publications
5
121
3
17
Order By: Relevance
“…All of these studies were primarily adult studies and CDI was not mentioned as an opportunistic infection. One adult study concluded no increased rate of serious bacterial infection in IBD patients on biologic (infliximab) therapy, including CDI, although the risk of CDI was increased by three times with corticosteroid use (14). This study primarily included adult CDI patients who required inpatient hospitalizations and excluded outpatient CDI diagnosis to overcome technical difficulties in analysis.…”
Section: Discussionmentioning
confidence: 99%
“…All of these studies were primarily adult studies and CDI was not mentioned as an opportunistic infection. One adult study concluded no increased rate of serious bacterial infection in IBD patients on biologic (infliximab) therapy, including CDI, although the risk of CDI was increased by three times with corticosteroid use (14). This study primarily included adult CDI patients who required inpatient hospitalizations and excluded outpatient CDI diagnosis to overcome technical difficulties in analysis.…”
Section: Discussionmentioning
confidence: 99%
“…La inmunosupresión también es un importante factor de riesgo. En un estudio reciente 40 , el tratamiento con corticoesteroides se ha asociado con ICD en pacientes con EII. El efecto de los corticoesteroides no se encontró que sea dosis o duración dependiente.…”
Section: Poblaciones Especialesunclassified
“…Studies on imumunosuppression with corticosteroids have also reported conflicting results, some finding no association with the risk of CDI in IBD patients, others reporting an increased risk of CDI (36). Schneeweiss et al (36) found that corticosteroid initiation tripled the risk of CDI among the IBD patients (relative risk 3.4, 95% CI 1.9-6.1), while no such association with the initiation of immunomodulators or biologics (infliximab) was found. Biological agents (e.g., infliximab, adalimumab) are not associated with increased risk of CDI in IBD patients (36), nor is the use of aminosalicylates (34).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Schneeweiss et al (36) found that corticosteroid initiation tripled the risk of CDI among the IBD patients (relative risk 3.4, 95% CI 1.9-6.1), while no such association with the initiation of immunomodulators or biologics (infliximab) was found. Biological agents (e.g., infliximab, adalimumab) are not associated with increased risk of CDI in IBD patients (36), nor is the use of aminosalicylates (34). PPI use in non-IBD patients has been suggested to increase the risk for CDI (6), but other studies did not find any association between PPI use and CDI in IBD patients (10).…”
Section: Risk Factorsmentioning
confidence: 99%